Analysis on the expression and function of a chicken-type and goose-type lysozymes in Chinese giant salamanders Andrias davidianus. (July 2017) - Yang, Hui; Liu, Ranran; Cui, Dan; Liu, Haixia; Xiong, Dongmei; Liu, Xiaolin; Wang, Lixin
Abstract: Lysozymes as an important immune factor, play vital roles in innate immune response against pathogen infection. In the present study, one c-type and g-type lysozymes were identified from Chinese giant salamander ( Andrias davidianus ). They shared highly conserved structural features with lysozymes from other species. Spatial expression analysis revealed that AdlysC transcript was most abundant in liver and stomach, and least in muscle and brain. In contrast, the expression level of AdlysG was most abundant in liver and least in muscle and skin. The transcription level of c-type and g-type lysozymes were up-regulated after Aeromonas hydrophila infection in liver and spleen, indicating their participations in the immune response. Moreover, the recombinant AdlysC and AdlysG protein were produced and purified, and were used to investigate the lysozyme activity at different pH and temperatures. The optimal lytic activity was determined at pH 6.0 and at a temperature of 30 °C. Through the minimal inhibitory concentration test, the rAdlysC and rAdlysG exhibited apparent antibacterial activity against both Gram-positive and Gram-negative bacteria with a variable concentration. In conclusion, it is the first report of lysozymes in A. davidianus, and c-type and g-type lysozymes should be involved in the innate immune response of A. davidianus. Highlights: One c-type and g-type lysozymes genes were identified and characterized from Andrias davidianus. AdlysC transcripts were most abundant in liver and stomach, while AdlysG were most abundant in liver. Both AdlysC and AdlysG could be up-regulated in liver and spleen after Aeromonas hydrophila infection. The optimal lytic activities of recombinant AdlysC and AdlysG were determined at pH 6.0 and at a temperature of 30 °C. Recombinant AdlysC and AdlysG enzymes exhibit antibacterial activities with a variable concentration.